Penyusunan Bahan Ajar (Buku) Berbasis Teori Dan Praktik Pada Mata Kuliah Pengenalan Bisnis Di Prodi Kewirausahaan Universitas Negeri Medan - Sabda Dian Nurani Siahaan; Aurora Elise Putriku; Lenti Susanna Saragih (Jurnal Dimensi Pendidikan dan Pembelajaran, 2023)
The Faculty of Economics, Universitas Negeri Medan is one of the educational institutions that plays an active role in organizing Entrepreneurship education. The problem found in the Entrepreneurship Study Program is the lack of teaching materials owned by lecturers to teach courses. Another problem is the lack of optimal implementation of practice in Entrepreneurship learning. This study aims to compile teaching materials in the Business Introduction course based on Theory and Practice. This research is a Research and Development (RnD) using the ADDIE development model which consists of 5 (five) stages of implementation, namely: (1) Analysis, (2) Design, (3) Development (4) Implementation, and (4) Evaluation. The data analysis techniques used in the study include 3 (three) types, Validity, Practicalis, and Effectiveness. The results showed that the resulting book was in the very decent category with a validity score of 99.34%. The results of the practicalist test show that books are very practical to use in learning with a score of 90.79%. Based on the effectiveness test, the average score of the student pretest is lower than the postest score, and the significance value obtained is 0.00